Isolation Of Cellulose from waste paper for the preparation of cellulosic beads - Sia, Alice Wei Chen (Universiti Malaysia Sarawak, UNIMAS, 2013)
Cellulose had been extracted from wastepaper through pretreatment, deinking and dissolution process for the preparation of cellulose beads. After dissolution of cellulose, regeneration of cellulose beads was conducted by water-in-oil emulsion. Cellulose solution was added drop by drop into the water-in-oil emulsion to form cellulose beads. The sizes of the cellulose beads were controlled by concentration of cellulose solution and concentration of surfactant. The physical and chemical properties of the cellulosic fibers and beads were investigated by FTIR and SEM. FTIR had been used to determine the presence of cellulose in cellulose beads. The surface morphology of the cellulose beads was characterized by SEM.